Isolation of bacteriophage with antimicrobial activity against Shigella Dysenteriae from sewage sample - Fahad, Dewan Al; Mustafiz, Tasmia Binta (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2019.